Investigation of Heat and Moisture Transport in Bananas during Microwave Heating Process - Wisara Thuto; Kittichai Banjong (My University, 2019)
The numerical method was used to investigate heat and moisture transport during dehydration of bananas from microwave heating. COMSOL multi-physics software was employed to perform the simulation task. A banana is defined as a porous medium. It has constituents of water, vapor, air as the liquid phase and a solid porous matrix. The numerical results of this study were validated with experimental data. The profiles of moisture, vapor and pressure are discussed in this study. Moreover, the effects of the ripening stages of the banana are examined. A higher heat flux was observed from the beginning period along with the increasing time steps until 50 s. Heat generation decreased during 50 s to 60 s, coinciding with a small rise in temperature, but the temperature gradient remained constant. The temperature distribution of both unripe and ripe banana samples was non-uniform. At the center of the banana, the temperature increased rapidly and reached its highest temperature with the negative temperature gradient toward the boundary surface. More heat generation was observed around the center region of the banana. This was due to higher moisture in comparison with the boundary surface. Heat and moisture were transported from the center of the banana to its surface. The water convective flux peaked around 11 mm from the center. The vapor pressure peaked at the center for all cases. Less heat generation within unripe bananas was observed due to the lower moisture content.
Keywords: Temperature Gradient; Food Drying and Modeling